PEMBERIAN CUTI HAID SEBAGAI PENERAPAN CSR TERHADAP KINERJA PEKERJA WANITA DI SURABAYA - Dedy Triyono; Feliciana Tjitrohartoko (LPPM UNISDA, 2022)
Abstract: In recent years, Corporate Social Responsibility or CSR has become a concern for many companies. This can be seen from the number of companies that have started to report on the various social and environmental initiatives they have undertaken in order to improve their CSR performance. An example of the implementation of CSR that a company can do is to comply with government regulations and pay attention to the welfare of its workers. The author feels the need to analyze the provision of menstrual leave as the implementation of CSR in Surabaya companies. This study aims to determine the effect of giving menstruation leave as the implementation of CSR on the performance of female workers in Surabaya. The research method used is interviews. The result of this research is that female employees are given the right to maternity and maternity leave. However, for the right to menstrual leave, so far there is no company policy that regulates the granting of the right to menstrual leave. This problem can have an impact on the performance of female employees who continue to come to work in the first days of menstruation because of pain and discomfort that can interfere with work activities so that their performance is not optimal. Keywords: CSR, the welfare of workers, the provision of menstrual leave Abstrak: Dalam beberapa tahun terakhir ini, Corporate Social Responsibility atau CSR telah menjadi perhatian bagi banyak perusahaan. Hal ini dapat dilihat dari banyaknya perusahaan yang mulai melaporkan berbagai inisiatif sosial dan lingkungan yang telah mereka lakukan dalam rangka meningkatkan kinerja CSR mereka. Contoh wujud penerapan dari CSR yang dapat dilakukan perusahaan adalah mematuhi peraturan pemerintah dan memperhatikan kesejahteraan pekerjanya. Oleh karena itu, penulis merasa perlu untuk menganalisis pemberian cuti haid sebagai penerapan CSR dalam perusahaan-perusahaan di Surabaya. Penelitian ini bertujuan untuk mengetahui pengaruh pemberian cuti haid sebagai penerapan CSR terhadap kinerja pekerja wanita di Surabaya. Metode penelitian yang digunakan adalah wawancara. Hasil dari penelitian ini adalah para karyawati diberikan hak untuk cuti hamil dan melahirkan. Akan tetapi, untuk hak cuti haid, selama ini belum ada kebijakan perusahaan yang mengatur mengenai pemberian hak cuti haid tersebut. Masalah ini dapat berdampak kepada kinerja para karyawati yang tetap masuk kerja pada hari-hari pertama haid dikarenakan rasa nyeri dan tidak nyaman yang dapat mengganggu aktivitas kerja sehingga kinerjanya menjadi tidak maksimal. Kata Kunci: CSR, kesejahteraan pekerja, pemberian cuti haid